An Obesity Risk SNP (rs17782313) near the MC4R Gene Is Associated with Cerebrocortical Insulin Resistance in Humans. (3rd June 2011) - Tschritter, Otto; Haupt, Axel; Preissl, Hubert; Ketterer, Caroline; Hennige, Anita M.; Sartorius, Tina; Machicao, Fausto; Fritsche, Andreas; Häring, Hans-Ulrich
Abstract : Activation of melanocortin-4 receptor (MC4R) by insulin sensitive neurons is a central mechanism in body weight regulation, and genetic variants in the MC4R gene (e.g., rs17782313) are associated with obesity. By using magnetoencephalography, we addressed whether rs17782313 affects the cerebrocortical insulin response. We measured the cerebrocortical insulin response by using magnetoencephalography in a hyperinsulinemic euglycemic clamp (versus placebo) in 51 nondiabetic humans (26 f/25 m, age 35 ± 3 years, BMI 28 ± 1 kg/m 2 ). The C-allele of rs17782313 was minor allele (frequency 23 % ), and the genotype distribution (TT 30, TC 19, CC 2) was in Hardy-Weinberg-Equilibrium. Insulin-stimulated cerebrocortical theta activity was decreased in the presence of the C-allele (TT 33 ± 16 fT; TC/CC − 27 ± 20 fT; P = .023 ), and this effect remained significant after adjusting for BMI and peripheral insulin sensitivity (P = .047 ). Cerebrocortical theta activity was impaired in carriers of the obesity risk allele. Therefore, cerebral insulin resistance may contribute to the obesity effect of rs17782313.